Association between family history and severity of coronary artery disease in a nationwide sample of patients with a first time myocardial infarction. (14th October 2021) - Said, M; Wahrenberg, A; Warnqvist, A; Jernberg, T; Witt, N; Svensson, P
Abstract: : Having an early family history of coronary artery disease (CAD) is strongly associated with incident cardio-vascular disease. In younger patients with acute coronary syndrome, an association between family history and the severity of CAD, determined by the number of affected coronary arteries diagnosed through coronary angiography, has been reported. However, it is unknown if these findings apply to unselected patients with a first-time myocardial infarction (MI) and whether an early family history of other atherosclerotic cardiovascular diseases (ASCVD) affect CAD severity. Therefore, our objective was to investigate the association between a family history of ASCVD and the extent of CAD determined by coronary angiography findings in a large nationwide sample of patients with a first-time MI. Material and methods: This study included a consecutive sample of 22, 686 one-year survivors of first-ever MI aged, 18 to 76 years, identified in the national register SWEDEHEART. Attending the standardized 1-year revisit after MI, from 2006 through 2013. First-degree relatives, defined as parents and full siblings, were identified in the Swedish Multi-Generation Register and data on historical hospitalisations and deaths were extracted. The exposure was defined as having a first-degree relative with records of early ASCVD, defined as a register-verified hospitalisation due to myocardial infarction, any angina with coronary revascularization, stroke or cardiovascular death before the age of 55 in male or 65 years in female relatives. The primary outcome was severity of CAD categorized to four groups: zero-, single-, two- or three-vessel disease as registered in SWEDE-HEART. Left main stem disease was included in the three-vessel category. The distribution of the CAD severity categories was compared between those with and without an early family history of ASCVD using multinomial logistic regression, adjusted for age and sex and using single-vessel disease as the reference group. Results: We included 22 686 participants (median age 63 [IQR 57–68] years; 27% women), of which 1450 had a family history of early ASCVD. A total of 2134 patients did not have any significant obstructive findings at the first coronary angiography, 10 951 patients had single-vessel disease, 5516 patients had two-vessel disease and 3970 patients had three-vessel or main stem disease. Both two-vessel disease (RRR 1.31, 95% CI 1.14–1.50) and three vessel and/or left main stem disease (RRR 1.29, 95% CI 1.1–1.51) were more common in patients with early family history of ASCVD when adjusting for age and sex, whereas no significant angiographic disease was less common (RRR 0.76, 95% 0.61–0.95). Conclusion: Patients with a first-time MI and a family history of early ASCVD have an approximately 30% higher risk of advanced coronary artery disease, with more than two affected coronary vessels or left main stem disease. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Swedish Heart and Lung Association (Riksförbundet HjärtLung)